1990
DOI: 10.1021/ac00206a026
|View full text |Cite
|
Sign up to set email alerts
|

Maleic acid/ammonium hydroxide buffer system for preconcentration of trace metals from seawater

Abstract: The differential binding of two chiral analytes on two different Pirkle phases was simulated with atomistic modeling. These results were described and compared with earlier work. The results from this work taken together with our earlier results allow us to state the following: (1) The computational protocol we employ seems to be valid; we always predict the correct retention order and we can qualitatively determine separability factors.(2) The intermolecular potential energy surfaces describing the binding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The pH of the acidified seawater samples was raised to ~5.5 by adding concentrated NH 4 OH and buffering with Maleic Acid/Ammonium Hydroxide (pH=5.8. Pai et al, 1990). Two mL of Biorad ® Chelex 100 resin (in 2N HNO 3 ), 100-200 mesh, were packed in a Biorad ® polyprep column (bed volume: 2 mL, conical, 0.8 cm mean internal diameter, 4 cm height; 10 mL reservoir).…”
Section: Transition Metals Separation From Seawater Matrixmentioning
confidence: 99%
“…The pH of the acidified seawater samples was raised to ~5.5 by adding concentrated NH 4 OH and buffering with Maleic Acid/Ammonium Hydroxide (pH=5.8. Pai et al, 1990). Two mL of Biorad ® Chelex 100 resin (in 2N HNO 3 ), 100-200 mesh, were packed in a Biorad ® polyprep column (bed volume: 2 mL, conical, 0.8 cm mean internal diameter, 4 cm height; 10 mL reservoir).…”
Section: Transition Metals Separation From Seawater Matrixmentioning
confidence: 99%
“…Several investigators have reported (Figura P. and McDuffie B., 1980,) that the effect of pH is an important factor for the binding of polyvalent metal ions into the amino-diacetate groups which act as chelating groups in the chelex-100 resin. However, the efficiency of the process depends on each possible combination of the loaded volume of sample, eluent amount, analyte (Pai et al, 1990) species, resin type and effect of pH adjusted by ammonium hydroxide/ maleic acid, as explained by Pai et al (1990). Maleic/ammonia buffer system is suitable for pH adjustment in the range of 2.0 -9.0.…”
Section: Recovery (%) When Eluted Bymentioning
confidence: 99%
“…The use of ion exchange resin is another option in order to overcome the problem of interference due to the salt matrix. It is well known that Chelex-100 cation-exchange resin has been employed in extracting cations from salt media in environmental samples such as sea water (Pai et al, 1990. ) and biological samples such as human fluid (Sun and Huang, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper describes a routine procedure for on-board operation of the Chelex-100 pre-concentration, with minimal maneuver. The principle is based generally on the method reported previously (Pai, 1988;Pai et al, 1988) but uses ammonium maleate as a buffer (Pai et al, 1990) instead of conventional ammonium acetate, and uses a more practical hanging bottle technique to avoid operational contamination. To demonstrate the applicability and precision of the method, a spiking experiment was carried out on board the R/V "Ocean Researcher I" at a station in the northern South China Sea, 100 km from Kaoshuing Harbour, Taiwan.…”
Section: Introductionmentioning
confidence: 99%